An Artistic Exploration of Inattention Blindness† - Levy, Ellen K. (Frontiers in Human Neuroscience, 2012)
An experiment about inattention blindness was conducted within the context of an art exhibition as opposed to a laboratory context in order to investigate the potential of art as a vehicle to study attention and its disorders. The project utilized a flash animation, Stealing Attention, that was modeled after the movie by Simons and Chabris (1999) but with significant experimental differences, involving context and staging, the emotional salience of the objects depicted, and the prior art viewing experience of participants. The study involved two components: observing if viewers watching an animation in a gallery could be distracted from noticing the disappearance of stolen museum antiquities (the targets) by the overlaid flashing images of a card game (the distractors) and then observing whether repetition of the depicted targets throughout the gallery installation could facilitate a re-direction of attention that allowed viewers to perceive the targets not initially noted in the animation. My findings were that, after viewing the entire installation and then re-viewing the animation, 80% of the viewers who did not initially remark on the targets in the animation were then able to see them. The discussion elaborates on these findings and then considers ways in which the implications of inattention blindness paradigms might be more fully rendered by uniting insights from the two disciplines of art and neuroscience than by either alone.